INTEGRATION OF COMPUTER GAMES INTO THE LEARNING PROCESS OF PRIMARY SCHOOLS: MODELS AND STRATEGIES. (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
This article explores the possibilities and strategies for integrating computer games into the primary school educational process. The study examines the educational effectiveness of games, their role in enhancing students' engagement, and their potential to motivate learners. A mixed-methods approach was utilized, including pre- and post- intervention assessments, teacher interviews, and classroom observations. The findings indicate that game-based learning can significantly improve academic performance and cognitive skills while highlighting challenges such as technical limitations and teacher preparedness.